2020
DOI: 10.1542/hpeds.2019-0259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Sociodemographic Factors Associated With Human Donor Milk Supplementation in Term Newborns

Abstract: To identify differences between healthy term newborns supplemented with human donor milk (HDM) and those supplemented with infant formula. We hypothesized that sociodemographic and clinical distinctions exist between newborns receiving different milk types.METHODS: This retrospective study included term newborns admitted to the postpartum unit between March 2017 and April 2019 with $1 supplemental feeding with HDM or formula for indications other than hypoglycemia. Maternal and newborn data were abstracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Conversely, affordability may be an obstacle for those with lower incomes, which motivates them to feed the mothers’ own milk. Other studies have shown that when PDM is paid for by private health insurance, this is the case [ 30 , 31 ]. Similarly, disparities in access to PDM according to race/ethnicity, socio-economic status, and access to private health insurance has been reported in the United States [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, affordability may be an obstacle for those with lower incomes, which motivates them to feed the mothers’ own milk. Other studies have shown that when PDM is paid for by private health insurance, this is the case [ 30 , 31 ]. Similarly, disparities in access to PDM according to race/ethnicity, socio-economic status, and access to private health insurance has been reported in the United States [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Policies and protocols to expand PDHM supplementation to infants in postnatal units may be similarly ineffective in closing gaps in its access and utilization due to structural racism, institutional racism, and individual health care provider racial biases. 35 , 50 , 61 , 62 Although well infants at NCWH may receive supplementation with PDHM when it is available, its use may depend on prenatal communication of this health care service, whether a health care provider offers it, or if a parent requests PDHM.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Nonetheless, even in hospitals with policies that make it possible for well newborns to receive PDHM, there have been reports of racial and ethnic disparities in its use. 61 , 62 …”
Section: Introductionmentioning
confidence: 99%
“…In recent qualitative studies of mothers, authors reported a range of perceptions including beliefs that donor milk was temporary and formula was the ongoing plan, donor milk was unfamiliar, and donor milk was "healthier" and "natural." 34,35 In recent studies, researchers have also reported lower use of donor milk in the level 1 nursery setting among nonwhite, 14,36 non-English-speaking mothers 36 and those with public insurance, 14,36 suggesting that maternal cultural differences or biases against donor milk use may exist or that nursery providers may have biases in delivery of education or recommendations for donor milk use toward certain groups of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…11 Generalizability of these findings to the rest of the United State is limited because responses were restricted to a single geographic area and donor milk use is known to vary by US region. Other evidence of dissemination of donor milk use in the level 1 nursery setting includes a published report of donor milk polices among 15 hospitals, 12 a report of donor milk used to treat hypoglycemia 13 and other conditions 14 at a single center, and reports from individual hospitals describing their donor milk programs. [15][16][17] Estimation of the national prevalence of donor milk programs in level 1 nurseries is needed to understand the extent that this practice has emerged in the past decade.…”
mentioning
confidence: 99%